“Grocery Empire” board game / Nur Syahirah Saharudin ... [et al.] - Saharudin, Nur Syahirah; Mohammad Faizal, Nur Fifie Af; Nasharudin, Fariha; Mazlan, Masyitah Ellysa; Abdul Wahid, Ahmad Syafiq; Wan Mohd Yasin, Wan Nurhafizah Fatin; Sa’ari, Juan Rizal (Universiti Teknologi MARA, Kedah, 2023)
Let us introduce our game innovation called “Grocery Empire”. This game brings the concept of spending in purchasing and managing groceries. The creation of this game happened to give fun to university students, besides the added new diverse features. This game is very suitable for people who want a new twist. The objective of this game is to teach students, enlightening them on the ways to manage their expenses on groceries and to develop essential life skills related to budgeting, financial responsibility and healthy eating habits. In addition, the knowledge gained from the board game can enhance the ability of an individual to manage their financial activities and thus contribute to the country's economic development. This game is created to solve students' problems of having limited financial resources, which makes it challenging to allocate sufficient funds for groceries while balancing other essential expenses. The difference between our board game and the rest of other board games out there is, we mainly focus on teaching the players on how to manage their expenses, specifically on grocery items to develop financial awareness on a daily basis. “Groceries Empire” includes strategy in choosing the cheapest grocery items and problem-solving components, encouraging players to consider financial decisions with choosing the most affordable stores to purchase grocery items cautiously. Students will also learn to differentiate between wants and needs. Our target market is university students, because they represent a crucial role in the market sector with distinct concerns. Our commercialization platforms include collaborating with grocery shops, food producers and even educational institutions which enable them to manage their groceries budget more effectively by providing incentives such as discounts or special deals, substituting the Chance Cards in Groceries Empire that offer exclusive savings or sales on grocery products to implement the game into their daily lives.